Does authentic leadership influences performance of individuals in presence of trust and leader member exchange: an evidence from health care sector - Hafiz Ghufran Ali Khan; Muhammad Anwar Khan; Muhammad Iftikhar Ali; Sultan Salem; Sobia Rashid; Hafsah Zahur (Cogent Business & Management, 2022)
Authentic leadership is attracting the researcher's interest since last decade. For the first time, this research examines the employee-centered aspect of authentic leadership, trust, leader member exchange (LMX) and individual performance with sequential mediation approach. Data were collected from 320 employees working in hospitals/health sector of Pakistan. Findings of the current study confirm significant and positive effect of the authentic leadership with individual performance connected both directly and indirectly through mediating effect of trust and LMX. Further, it is also revealed that authentic leadership creates trustworthy environment among the followers that enhances employee LMX and subsequently improves their job performance. This research delivers novel results of the sequential mediating effects of constructs from one aspect and from other aspect it has integrated four important variables in one model. Theoretical and practical implications along with future recommendations are presented at the end too.
Keywords: 650; Trust; Authentic Leadership; Health sector; individual performance; leadership style; LMX